Neoadjuvant programmed death ligand-1 with chemotherapy versus chemotherapy alone for limited-stage small-cell lung cancer: a retrospective study - Zhi Yang; Yan-qing Wang; Xiujun Chang (Frontiers in Oncology)
Summary backgroundOur objective was to investigated the safety and feasibility of neoadjuvant treatment with PD(L)1 inhibitors and chemotherapy followed by surgery for resectable SCLC.MethodsIn this retrospective cohort study, we included patients with limited-stage SCLC treated with neoadjuvant chemotherapy (with/without)ICI at Beijing Chest Hospital (Beijing, China) between July 2020 and December 2021. Seventeen patients with LD-SCLC were enrolled in the study. Two groups were assigned for further statistical analysis: neoadjuvant chemotherapy (group C), in which only preoperative chemotherapy was administered; and neoadjuvant ICI (group I), in which surgery was combined with both preoperative ICI and chemotherapy. Patient demographics, radiological and pathological evaluations of tumor response, surgical information, toxicity profiles, tumor marker and follow-up results of both groups were evaluated.Results17 patients were included in this retrospective study, of which, 11 patients received ICI and chemotherapy-containing regimens and 6 patients received neoadjuvant chemotherapy only. Herein, we firstly reported that neoadjuvant PD-(L)1 blockade plus chemotherapy led to a pCR rate of 45.5% in patients with limited-stage small cell lung cancer. The MPR rate of 72.7% due to treatment with neoadjuvant PD-(L)1 blockade plus chemotherapy group (group I) was significantly higher than those in the traditional neoadjuvant chemotherapy group (16.7%)(group C). We first found that ProGRP is a good the evaluation indicator for neoadjuvant immunotherapy in small cell lung cancer and found that the ProGRP levels decreased significantly in both group after neoadjuvant therapy, and it was more obvious in group I(P=0.003).All Of the 17 patients (100.0%) had R0 resection. There were no perioperative deaths.ConclusionsNeoadjuvant immunotherapy shows lower toxicity and fewer perioperative complications. ICI combined chemotherapy can achieve more pathological relief and clinical benefits in the neoadjuvant treatment of LS-SCLC without increased irAE and perioperative complications. However, the small sample size limits the reliability of the research.